The brain network of expectancy and uncertainty processing. - Andrés Catena (Public Library of Science (PLoS), 2012)
Background The Stimulus Preceding Negativity (SPN) is a non-motor slow cortical potential elicited by temporally predictable stimuli, customarily interpreted as a physiological index of expectancy. Its origin would be the brain activity responsible for generating the anticipatory mental representation of an expected upcoming event. The SPN manifests itself as a slow cortical potential with negative slope, growing in amplitude as the stimulus approximates. The uncertainty hypothesis we present here postulates that the SPN is linked to control-related areas in the prefrontal cortex that become more active before the occurrence of an upcoming outcome perceived as uncertain. Methods/findings We tested the uncertainty hypothesis by using a repeated measures design in a Human Contingency Learning task with two levels of uncertainty. In the high uncertainty condition, the outcome is unpredictable. In the mid uncertainty condition, the outcome can be learnt to be predicted in 75% of the trials. Our experiment shows that the Stimulus Preceding Negativity is larger for probabilistically unpredictable (uncertain) outcomes than for probabilistically predictable ones. sLoreta estimations of the brain activity preceding the outcome suggest that prefrontal and parietal areas can be involved in its generation. Prefrontal sites activation (Anterior Cingulate and Dorsolateral Prefrontal Cortex) seems to be related to the degree of uncertainty. Activation in posterior parietal areas, however, does not correlates with uncertainty. Conclusions/significance We suggest that the Stimulus Preceding Negativity reflects the attempt to predict the outcome, when posterior brain areas fail to generate a stable expectancy. Uncertainty is thus conceptualized, not just as the absence of learned expectancy, but as a state with psychological and physiological entity.